Does real exchange rate depreciation increase productivity? Analysis using Korean firm‐level data. (25th July 2017) - Choi, Bo‐Young; Pyun, Ju Hyun
Abstract: We examine the effects of real exchange rate (RER) depreciation shocks on firm productivity. Using the firm‐level data of Korean manufacturing industries for 2006–13, we distinguish between yearly RER movement and persistent RER depreciation during 2007–09 and analyse how each affects productivity. We find the positive effect of RER depreciation on productivity among exporters, and this positive effect increases with higher export exposure. However, the positive productivity gain disappears when the depreciation persists. Our findings suggest that while immediate depreciation leads to productivity upgrade via price competitiveness and scale expansion, persistent depreciation nullifies the productivity gain by slackening the innovation effort.